Market-to-book ratio and conditional conservatism: firms' voluntary expensing of employee stock options. Issue 2 (19th August 2014) - Wakil, Gulraze
Abstract : Purpose: This paper seeks to examine the relationship between firms' decisions to expense employee stock options (ESOs) under the voluntary period of SFAS 123 and their market-to book (MTB-1) ratio and conditional conservatism. Conservatism is chosen because, even though expensing of ESOs is a conservative accounting treatment, it is not obvious how the decision would be related to the MTB-1 ratio and conditional conservatism, particularly because the MTB-1 is a long run measure of conservatism and the decision to voluntarily expense is examined over two years. The setting provides a unique opportunity to assess how two major proxies of conservatism are related. Design/methodology/approach: Using firms listed in the S&P 1500 index, firms that expensed ESOs are compared to firms that disclosed only in the financial statements. The main comparison uses a logistic regression. Findings: During the period when expensing ESOs was voluntary, SFAS 123, the MTB-1 ratio was negatively associated with ESO expense recognition, but conditional conservatism was positively associated with ESO expense recognition. The former is attributed to incentives of conservatism and the latter to the tenet of conservatism tending to reduce income. Research limitations/implications: The findings add to the literature/controversy on the negative relationship between the MTB-1 ratio and conditional conservatism. More important, they support using more than one measure of conservatism in studies that involve accounting conservatism. A limitation is that the findings are specific to voluntary ESO expense recognition. Originality/value: This is the first study to examine how conservatism affects the choice to recognize an item on the financial statements or disclosure only. In addition, the study shows that firms were willing to incur real costs from their financial reporting.